The role of molluscs in monitoring marine pollution and its connection to climate change and ESG - Chee Kong Yap; Kennedy Aaron Aguol; Meng Chuan Ong; Wan Mohd Syazwan; Rosimah Nulit; Hideo Okamura; Yoshifumi Horie; Mohamad Saupi Ismail; Ahmad Dwi Setyawan; Krishnan Kumar; Wan Hee Cheng; Chee Seng Leow (Enviro Research Publishers, 2024)
Molluscs possess a unique capability to filter and remove pollutants from water, offering a natural and effective solution to combat marine pollution. Their filtration process not only enhances water quality but Article History also mitigates the detrimental impacts of contaminants on marine ecosystems. As climate change introduces unprecedented challenges, the resilience of molluscs—particularly in adapting to rising temperatures and ocean acidification—highlights their critical role in sustaining marine ecosystem balance. This paper reviews the literature on molluscs from 1874 to 2024, as documented in the Scopus database, analyzing 5,757